THE USE OF EFFECTIVE STRATEGIES FOR IMPROVING LEARNERS’ READING COMPREHENSION - Salimova Nozima (Galaxy International Interdisciplinary Research Journal, 2024)
The ability to process literature, understand its meaning, and integrate it with what the reader already knows is referred to as reading comprehension. Reading comprehension is strongly dependent on learners’ ability to comprehend the collection of words. Reading proficiency can be acquired through both excellent education and personal experience. Two levels of processing are activated during reading comprehension. There are two levels: shallow and deep. Neuroimages are used to explore this process. Reading technique is a broad phrase that refers to the deliberate and explicit acts that assist readers in translating print to meaning. Reading strategies varies depending on the circumstances. Reciprocal teaching is one of the reading strategies. This entails making predictions, summarizing, and asking questions. The method of conversation or instructional directives assists pupils in visually comprehending material utilizing higher level thinking. There are numerous tactics to employ, ranging from activation to dialogue.